2000
DOI: 10.1177/156482650002100210
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the production and consumption of vitamin A–rich fruits and vegetables: Lessons learned in taking the Bangladesh homestead gardening programme to a national scale

Abstract: Micronutrient malnutrition affects more than 20 million children and women (at least 50% of this population) in Bangladesh. The diets of more than 85% of women and children in Bangladesh are inadequate in essential micronutrients such as vitamin A, largely because adequate amounts of foods containing these micronutrients are not available, or the household purchasing power for these foods is inadequate. In Bangladesh and many other developing countries, large-scale programmes are needed to make a significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 2 publications
(2 reference statements)
2
74
0
Order By: Relevance
“…The increased income achieved via household gardening was found in one study to be used mainly for the purchase of food (Talukder et al 2000). Increased income among women (Brun, Reynaud, and Chevassusagnes 1989) (who tend to take over gardening projects, even if initially targeted to men) and even women's decision-making power within the household (Bushamuka et al 2005) are often likely to be major benefits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased income achieved via household gardening was found in one study to be used mainly for the purchase of food (Talukder et al 2000). Increased income among women (Brun, Reynaud, and Chevassusagnes 1989) (who tend to take over gardening projects, even if initially targeted to men) and even women's decision-making power within the household (Bushamuka et al 2005) are often likely to be major benefits.…”
Section: Methodsmentioning
confidence: 99%
“…Large-scale programs have observed that benefits expand passively beyond the intervention areas to nearby communities (Greiner and Mitra 1995), (Talukder et al 2000), (Faber et al 2011). Biofortification and dissemination of sweet potatoes cost $9 to $30 per disability-life-year (DALY) gained (Meenakshi et al 2010), while that from VAS was estimated at the estimated cost effectiveness of VAS is $73 per DALY gained (Fiedler et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Third, home gardening, which is proposed as a means to ensure the availability of fruits and vegetables, might be possible in rural areas, but it may be improbable in populated areas factoring in costs and time to tend the garden (Stein et al, 2008). A study in Bangladesh demonstrated that technical assistance was required for home gardens to be effective in increasing vegetable consumption, and households needed a regular supply of quality seed and other inputs (Talukder et al, 2000). Additionally, human and institutional capacity may well be required to implement and monitor the program, and nutrition education to achieve behavioral changes (Stein et al, 2008).…”
Section: Alternatives To Reduce Vitamin a Deficiencymentioning
confidence: 99%
“…Poor women are the central target in this program. This program covered more than 860,000 households in Bangladesh by February 2000 [2].…”
Section: Introductionmentioning
confidence: 99%